THE BICYCLE'S STORY CREATIVITY AS A TECHNICAL COMPETENCE DURING HUNDREDS OF YEARS - Sándor, KISS (Trends in education, 2008)
Competences is one of the most often used ideas in the pedagogical literature today. One way of classification of different types of competences is in accordance of the different teaching fields. One of the main characters of the technical or technological competence is the creativity.